Ikhtiyâr al-Kalimât fî al-Âyât ‘an al-Jannah fî al-Qur’ân - Khairul Fuadi (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2021)
The Qur'an has perfect language in all aspects. We can see the height of language in aspects of phoneme selection, word selection, sentence choice and the effects it causes. Choosing the right diction will produce the right meaning and vice versa. in the context of the Qur'an, it can be seen that the accuracy of the words in the formation of each sentence so that the meaning is conveyed in its entirety in accordance with the desired message. Diction analysis is an activity to uncover or find out the practice of word choice by separating the dictions, including disentangling the structure and variety of diction. This paper will reveal the purpose of choosing certain words to represent a meaning perfectly by analyzing using a qualitative descriptive approach. That is using text as the basic capital to understand the facts. The facts described are the unique diction used in the Qur'an, especially the verses related to heaven. The results of this paper are to reveal the secret and purpose of each use of diction, which will have different meanings if using a different diction.